2012
DOI: 10.1021/ma301388j
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Segmental Dynamics in Cylindrical and Spherical Phases of Diblock Copolymers

Abstract: We have performed simulations of a simple bead-spring model for cylindrical and spherical phases of diblock copolymers. We have analyzed in detail the dynamic heterogeneity of the structural α-relaxation of the component confined in the minority domains. In analogy with previous investigations on the lamellar phase of the same bead-spring model, the analysis reveals moderate gradients of mobility in the investigated temperature range, which qualitatively probes time scales up to 100 ns. Thus α-relaxation times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This is consistent with recent computational investigations on the α-relaxation in bead−spring copolymers with lamellar, 18 cylindrical, and spherical morphologies. 19 A thorough experimental characterization of the segmental dynamics in the different morphologies of the PI−PDMS copolymers is beyond the scope of this work and will be shown elsewhere. 34 The most striking result from the present BDS experiments is the bimodal character of the NM relaxation of the PI blocks in the PI−PDMS lamellae, unlike the single NM peak observed in the cylindrical and spherical morphologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with recent computational investigations on the α-relaxation in bead−spring copolymers with lamellar, 18 cylindrical, and spherical morphologies. 19 A thorough experimental characterization of the segmental dynamics in the different morphologies of the PI−PDMS copolymers is beyond the scope of this work and will be shown elsewhere. 34 The most striking result from the present BDS experiments is the bimodal character of the NM relaxation of the PI blocks in the PI−PDMS lamellae, unlike the single NM peak observed in the cylindrical and spherical morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…15,17 Recent simulations confirmed this picture. 18,19 A recent study by Sanz et al 16 addressed the effect on the α-relaxation when the confining matrix crosses its glass transition temperature, T g , i.e., when going from a "hard" to a "soft" confinement. It was found that the low-T g (fast) component did not exhibit any discontinuity upon crossing the T g of the confining (slow) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially resolved measurements have suggested that this enhancement emerges from a layer of enhanced T g and suppressed dynamics adjacent to the substrate—a phenomenon that resembles the RAF. More broadly, examples of these effects also include alterations of glass formation behavior in nanolayered polymers, “bound rubber” layers in filled rubber, alterations in the T g of polymer nanocomposites, the emergence of “suppressed mobility domains” around ionic aggregates in ionomeric polymers, and shifts in the T g of block copolymers relative to homopolymers . Like the RAF in semicrystalline polymers, all of these systems exhibit evidence of a domain near internal or external interfaces in which dynamics and glass formation behavior are profoundly altered.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] While this fi eld has most heavily focused on polymers [ 4,6 ] and small molecules liquids [ 7,10,11 ] confi ned in thin fi lm or pore geometries, polymers with internal nanostructure, such as those shown [ 12 ] in Figure 1 , have been reported to exhibit similar alterations in dynamics for half a century or more. These observations include the following: deviations of T g from pure-state values in block copolymer nanodomains, noted as early as the 1960s; [13][14][15][16][17][18][19][20][21] shifts in segmental dynamics around particles in nanocomposites [22][23][24][25][26][27][28][29] and fi lled rubbers, [30][31][32][33][34] which are believed to contribute to mechanical reinforcement effects in these systems; observation of a rigid amorphous fraction with suppressed segmental dynamics and enhanced T g around crystalline domains in semicrystalline polymers; [ 35 ] and evidence of suppressedmobility domains surrounding ionic aggregates in ionomers. [36][37][38] Despite strong parallels in the phenomenology of near-interface dynamics in these materials, they have commonly been treated as fundamentally distinct systems, each with unique underlying physics.…”
Section: Introductionmentioning
confidence: 99%